Sinensetin serves as an AMPK activator to inhibit RANKL-induced osteoclastogenesis via osteoclast cytoskeleton reorganization - Yijie Gao; Rui Zhou; Xixi Lin; Zhijuan Liu; Yuangang Su; Haoyu Lian; Bin Lin; Xiaofei Ding; Shijie Liao; Xiangde Li; Jinmin Zhao; Jiake Xu; et al. (Journal of Translational Medicine)
Abstract Osteoporosis is a skeletal condition caused by an excess of osteoclasts, resulting in an imbalance in bone metabolism. Sinensetin (SIN), one of the main ingredients in citrus fruits, provides a variety of pharmacological properties, like antioxidant, but its effects on osteoporosis remains unknown. Herein, we explored at how SIN affected RANKL-induced osteoclastogenesis and ovariectomy (OVX)-induced osteoporotic mice. Our research found that SIN, without compromising cell viability, inhibited RANKL-mediated osteoclastogenesis and the NFATc1 signaling pathway in a concentration-dependent manner. Further, RNA sequencing analysis suggested that the molecular mechanism of SIN inhibitory effect on osteoclasts is related to the cytoskeleton reorganization. The results indicated that SIN prevents the cytoskeleton reorganization of preosteoclasts via the c-Src-mediated PI3K/PAK4/AKT signaling axis. Meanwhile, SIN enhanced the expression of phosphorylation and activity of AMP-activated protein kinase (AMPK) in response to RANKL. Further, SIN targets AMPK to reduce intracellular Reactive oxygen species (ROS) levels, thereby blocking c-Src activation. Finally, we verified that SIN inhibits osteoclast activity, thus preventing OVX-induced bone loss. These findings suggest that SIN serves as an AMPK activator that abrogates RANKL-induced osteoclastogenesis and OVX-induced bone loss via hindering cytoskeleton reorganization. Graphical abstract